Exploring the Writing Challenges Faced by First-Year EFL Students: A Qualitative Approach - Rosalia, Harnita; Saputri, Faradillah; S, Jumraini; Amir, Hasbiyah Srianah; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2025)
This study aims to identify the major writing difficulties faced by first-year students in English as a Foreign Language (EFL) contexts at Universitas Negeri Makassar. A qualitative research approach was employed, involving the analysis of students’ written assignments and in-depth interviews with 15 purposively selected participants. The findings reveal four key areas of difficulty: grammatical and sentence structure errors, limited vocabulary and inappropriate word choice, poor paragraph organization, and a lack of coherence and cohesion. In addition to these surface-level issues, the study uncovered several underlying contributing factors, including limited exposure to English outside the classroom, inadequate writing instruction, first language interference, emotional barriers, and excessive reliance on translation technology. These results indicate that students’ writing challenges are not solely rooted in linguistic deficiencies but are shaped by a broader ecosystem of influences that impact their development as academic writers. A deeper understanding of these factors is essential for designing more effective pedagogical interventions—ones that address both technical errors and the developmental needs of EFL learners.